A Simple Radiological Technique for Demonstration of Incorrect Positioning of a Foley Catheter with Balloon Inflated in the Urethra of a Male Spinal Cord Injury Patient - Subramanian Vaidyanathan; Peter L. Hughes; Bakul M. Soni (The Scientific World Journal)
In a male patient with cervical spinal cord injury, the urinary bladder may go into spasm when a urethral catheter is removed and a new Foley catheter is inserted. Before the balloon is inflated, the spastic bladder may push the Foley catheter out or the catheter may slip out of a small-capacity bladder. An inexperienced health professional may inflate the balloon of a Foley catheter in the urethra without realizing that the balloon segment of the catheter is lying in the urethra instead of the urinary bladder. When a Foley balloon is inflated in the urethra, a tetraplegic patient is likely to develop autonomic dysreflexia. This is a medical emergency and requires urgent treatment. Before the incorrectly placed Foley catheter is removed, it is important to document whether the balloon has been inflated in the urinary bladder or not. The clinician should first use the always available tools of observation and palpation at the bedside without delays of transportation. A misplaced balloon will often be evident by a long catheter sign, indicating excessive catheter remaining outside the patient. Radiological diagnosis is not frequently required and, when needed, should employ the technique most readily available, which might be a body and pelvic CT without intravenous contrast. An alternative radiological technique to demonstrate the position of the balloon of the Foley catheter is described. Three milliliters of nonionic X-ray contrast medium, Ioversol (OPTIRAY 300), is injected through the side channel of the Foley catheter, which is used for inflating the balloon. Then, with a catheter-tip syringe, 30 ml of sterile Ioversol is injected through the main lumen of the Foley catheter. Immediately thereafter, an X-ray of the pelvis (including perineum) is taken. By this technique, both the urinary bladder and balloon of the Foley catheter are visualized by the X-ray contrast medium. When a Foley catheter has been inserted correctly, the balloon of the Foley catheter should be located within the urinary bladder, but when the Foley catheter is misplaced with the balloon inflated in the urethra, a round opaque shadow of the Foley balloon is seen separately below the urinary bladder. This radiological study takes only a few minutes to perform, can be carried out bedside with a mobile X-ray machine, and does not require special expertise or preparations, unlike transrectal ultrasonography. When a Foley balloon is inflated in the urethra, abdominal ultrasonography will show an absence of the Foley balloon within the bladder. The technique described above aids in positive demonstration of a Foley balloon lying outside the urinary bladder. Such documentation proves valuable in planning future treatment, education of health professionals, and settlement of malpractice claims.